Histone Acetylation as a Regenerative Target in the Dentine-Pulp Complex - Yamauchi, Yukako; Duncan, Hal (My University, 2020)
If dental caries (or tooth decay) progresses without intervention, the infection will advance through the dentine leading to severe pulpal inflammation (irreversible pulpitis) and pulp death. The current management of irreversible pulpits is generally root-canal-treatment (RCT), a destructive, expensive, and often unnecessary procedure, as removal of the injurious stimulus alone creates an environment in which pulp regeneration may be possible. Current dental-restorative-materials stimulate repair non-specifically and have practical limitations; as a result, opportunities exist for the development of novel therapeutic strategies to regenerate the damaged dentine-pulp complex. Recently, epigenetic modification of DNA-associated histone ‘tails’ has been demonstrated to regulate the self-renewal and differentiation potential of dental-stem-cell (DSC) populations central to regenerative endodontic treatments. As a result, the activities of histone deacetylases (HDAC) are being recognised as important regulators of mineralisation in both tooth development and dental-pulp-repair processes, with HDAC-inhibition (HDACi) promoting pulp cell mineralisation in vitro and in vivo. Low concentration HDACi-application can promote de-differentiation of DSC populations and conversely, increase differentiation and accelerate mineralisation in DSC populations. Therapeutically, various HDACi solutions can release bioactive dentine-matrix- components (DMCs) from the tooth’s extracellular matrix; solubilised DMCs are rich in growth factors and can stimulate regenerative processes such as angiogenesis, neurogenesis, and mineralisation. The aim of this mini-review is to discuss the role of histone-acetylation in the regulation of DSC populations, while highlighting the importance of HDAC in tooth development and dental pulp regenerative-mineralisation processes, before considering the potential therapeutic application of HDACi in targeted biomaterials to the damaged pulp to stimulate regeneration.
PUBLISHED [GOLD]
Keywords: histone deacetylases; dentinogenesis; regenerative endodontics; dental pulp; acetylation; histone acetyltransferases